Time-domain OFDM carrier phase estimation for wireless sensor network syntonization - Tröger, Hans-Martin; Hartmann, Markus; Patino-Studencki, Lucila; Robert, Jörg; Heuberger, Albert (2016 26th International Telecommunication Networks and Applications Conference (ITNAC), 2016)
One of the most promising ways of bringing localization services to GPS denied areas is the use of wireless sensor networks. For time difference of arrival (TDOA) systems, the achievable accuracy highly depends on the synchronization accuracy between the sensor nodes. In this paper we describe a new algorithm that achieves an ultra-precise wireless frequency synchronization using OFDM signals. Especially for indoor environments, which typically suffer from multi-path propagation, significant improvements compared to state-of-the-art algorithms can be reached. An additional benefit of our algorithm is the low complexity, which allows for low-cost implementations. After the explanation of our concept and the algorithms, its simulated performance is evaluated.
CRIS-Team Scopus Importer:2024-11-19
Keywords: CFO; localization; multipath; OFDM; Signals of Opportunity; syntonization